Effect of tool shoulder geometry on lapped Al/CFRTP hybrid joint structure and strength made by pinless friction spot joining - Weihao Li; Peihao Geng; Ninshu Ma; Hidetoshi Fujii; Hong Ma (Journal of Materials Research and Technology)
Friction spot joining (FSpJ) has been proven to be a highly competitive process for fabricating hybrid joints composed of metal and carbon fibre-reinforced thermoplastic. However, previous research has rarely focused on optimizing joint performance by controlling thermal conduction through modifying tool structures. This study systematically explores the effect of the recessed tool shoulder geometry on mechanical strength of 6061-T6 Al alloy and carbon fibre-reinforced polyamide-6 (CF/PA6) pinless-FSpJ joint. An experimentally validated three-dimensional (3D) finite element model was built to investigate the heat generation and thermal conduction. Results show that the recessed tools with different external diameters achieve higher average interface strength in lap joints compared to flat shoulder tools. Under fixed plunge depth conditions, increasing the depth of the recessed area results in a lower rate of temperature rise and a more uniform temperature distribution during heating stage. As a result, the duration of resin decomposition in the molten state is further reduced, but the time in a single molten state is extended. This benefits the wetting process of molten resin on the silanized Al surface and subsequent chemical reaction with the silane film, while alleviating decomposition defects to a certain extent. The reduction in residual tension stress at the center of Al upper surface indirectly indicates the improving effect of increased recessed tool depth on the stress state of the joint.